Risk of Environmental Exposure to H7N9 Influenza Virus via Airborne and Surface Routes in a Live Poultry Market in Hebei, China - Zhang, Cheng; Guo, Kangkang; Cui, Huan; Chen, Ligong; Zhang, Chunmao; Wang, Xuejing; Li, Jiaming; Fu, Yingying; Wang, Zhongyi; Guo, Zhendong; Liu, Juxiang; Dong, Shishan (Frontiers in Cellular and Infection Microbiology, 2021)
Environmental transmission of viruses to humans has become an early warning for potential epidemic outbreaks, such as SARS-CoV-2 and influenza virus outbreaks. Recently, an H7N9 virus, A/environment/Hebei/621/2019 (H7N9), was isolated by environmental swabs from a live poultry market in Hebei, China. We found that this isolate could be transmitted by direct contact and aerosol in mammals. More importantly, after 5 passages in mice, the virus acquired two adaptive mutations, PB1-H115Q and B2-E627K, exhibiting increased virulence and aerosol transmissibility. These results suggest that this H7N9 virus might potentially be transmitted between humans through environmental or airborne routes.